2015
DOI: 10.1097/inf.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Viral and Bacterial Potential Pathogens in the Nasopharynx of Children With and Without Respiratory Symptoms

Abstract: Viruses are associated with different NP bacterial colonization patterns. Observed pathogens' associations may play a role in disease, and continuous surveillance is required to follow possible effects of interventions such as vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
4
16
0
5
Order By: Relevance
“…However, Yu et al reported that bacterial colonization following viral infection has no effect on clinical manifestation of ARIs [32]. Furthermore, the role of bacterial pathogens in ARI symptoms is ambiguous as recent studies of asymptomatic ARI cases reported frequent bacterial colonization [33] and our study also found comparable detection rates of S . pneumoniae in both asymptomatic and symptomatic children.…”
Section: Discussionsupporting
confidence: 55%
“…However, Yu et al reported that bacterial colonization following viral infection has no effect on clinical manifestation of ARIs [32]. Furthermore, the role of bacterial pathogens in ARI symptoms is ambiguous as recent studies of asymptomatic ARI cases reported frequent bacterial colonization [33] and our study also found comparable detection rates of S . pneumoniae in both asymptomatic and symptomatic children.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, patients often present an increasing proportion of pathogenic bacteria. 42 From the current data alone, it is not clear whether the differences in the bacterial community are secondary to Plasmodium infection or factors facilitating the infection in mosquitos.…”
Section: Discussionmentioning
confidence: 93%
“…One hundred nanograms of RNA was reverse‐transcribed using Superscript II and random hexamers (InVitrogen), according to the manufacturer's instructions. Polymerase chain reactions were performed using conditions of reaction and primers as described before …”
Section: Methodsmentioning
confidence: 99%
“…Polymerase chain reactions were performed using conditions of reaction and primers as described before. 16,17 The whole population (1207 samples) was tested for IFV, while 590 randomly selected samples (~300 per year) were tested for RV.…”
Section: Virologymentioning
confidence: 99%